KOMPETENSI SOSIAL GURU DALAM BERKOMUNIKASI SECARA EFEKTIF DENGAN SISWA MELALUI KEGIATAN PEMBELAJARAN BAHASA INDONESIA DI SD NEGERI REJOWINANGUN 3 KOTAGEDE YOGYAKARTA - Anggun Rahmawati; C. Indah Nartani (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: This research aim for understanding and get knowledge about teacher’s social ability able to communicate with student effectively by learning bahasa Indonesia,this type of research are descriptive and qualitative,the technique to collect the information are interview,observation, and documentation. The data analysis technique by doing data collection,data reduction,data presentation and conclusion, the results this type of research indicate that teacher’s social ability in communicate efectivly with student by learning bahasa Indonesia including social interaction with student,able to mastering many word in bahasa Indonesia in order to diliver better information,play role as mentor, give encouragement to make them active,and to be teacher we must not careless.Effort to upgrade teacher’s social ability including pay attention every stundent’s need,understand student’s characteristics,mastering the subject we want share,appy bahasa Indonesia in daily basis,try give them some feed to make communication effective,and make evaluation in every teacher The obstacles in effective cummonucation are including student not yet ready adapt in new environment, not pay attention when teacher explain,and few of them dislike bahasa Indonesia subject, the bahasa Indonesia material not well recived by the student.